The impact of global budget on the diffusion of innovations: the example of positron emission tomography in Taiwan - Che-Ming Yang (BMC, 2018)
Abstract Background The essence of global budget is to set a cap on the total national health insurance expenditure for a year, which is one form of prospective payment systems. It has always been argued that prospective payment, such as global budgeting, will deter the development of high-tech services in the healthcare industry. The objectives of this study are to explore the impact of global budgeting on the diffusion of high tech equipment in terms of utilization by using Positron Emission Tomography (PET) as an example. Methods The study population is the hospitals in Taiwan. We tried to compare the diffusion patterns of Computed Tomography (CT), Magnetic Resonance Imaging (MRI) and PET scanners among these hospitals by analyzing the National Health Insurance (NHI) Database from 1997 to 2010. Results From 2004 to 2010, 79,380 PET scans in total were performed under the NHI scheme. By the year 2010, the annual reimbursed scans have reached 19,700. The volume curve of cumulative PET services resembles an S diffusion curve with the R2 at 0.95. The results indicated the growth of cumulative PET service volume does correspond with the innovation diffusion model. The cumulative utilizations of CT, MRI and PET demonstrate good correlation with no significant difference in their growth rates. Conclusions Therefore, we can infer that even though PET was reimbursed after the implementation of global budgeting, its diffusion was not deterred by this cost containment measure when compared with CT and MRI in the same time span after the inauguration of the NHI.